EDUKASI KESEHATAN TERHADAP PEMILIHAN TEMPAT BEROBAT TRADISIONAL DAN KONVENSIONAL - Harahap, Nurul Dahlia; Rahmi, Sofia; Tarigan, Ratna Sari; Sembiring, Pintata; Harahap, Indah Putri (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
The success of a treatment is assessed based on the therapeutic effects achieved and the duration of the treatment. The choice of treatment place, whether traditional or conventional, is influenced by several parameters including age, occupation, education, gender, family support, and the use of health insurance. Based on that, health education was conducted in Mompang I Village, Halongonan Timur, Padang Lawas Utara. This activity was conducted to enhance the community's understanding of indications and side effects based on the place of treatment. Health education in the form of counseling was conducted on March 2, 2025, to 66 members of the community, with 37 people (56%) choosing conventional healthcare facilities for treatment. With this mechanism, the community will be more prudent in determining treatment for a health condition that requires medical intervention. From the responses, it was found that education and occupation factors have a strong correlation with the use of conventional medicine, while the use of traditional medicine is based on family support and has been used for generations.